Hybridization in wire arc additive manufacturing - Kapil, Sajan; Rajput, Atul Singh; Sarma, Ritam (Frontiers in Mechanical Engineering, 2022)
Wire Arc Additive Manufacturing (WAAM) can produce a near-net shape of an object within a short period due to its capability of high deposition rate compared with other metal Additive Manufacturing (AM) processes. The recent developments in the WAAM have increased its efficiency and cost-effectiveness in producing viable products. However, poor surface quality, porosities, residual stresses, distortions, and anisotropic mechanical properties are a few inherent challenges still associated with the WAAM, which necessitates the hybridization of this process. Hybrid-WAAM is a synergic integration of one or more deposition processes, manufacturing processes, layering strategies, raw stock materials, and machine tool kinematics that are fully coupled and affect part quality, functionality, and process performance. This paper comprehensively reviews different levels of hybridization in the WAAM to eliminate its associated challenges. These levels of hybridizations are classified into five categories: hybrid-deposition processes, hybrid-manufacturing processes, hybrid-layering strategies, hybrid-machine tools, and hybrid-raw stock. Furthermore, these levels of hybridization are mapped to eliminate the associated defects/challenges in the WAAM, which will help the readers select an appropriate level of hybridization.